(untitled) (Fiep Bulletin - online, 2013)
Through the literature review, this article aims to inform and bring the history of the circus, from its possible origins to the modern circus concept, recognizing its values and premises as secular art. The circus art as entertainment keep pace with companies since their beginnings, permeating the life of different people. It is difficult to accurately date the origin of this art; sometimes it is in China, sometimes in Greece or Egypt. And so the circus is built, as a form of enchantment, retreat and abstraction from the real world for Soares (1998). One of the major facts that inspired the circus art was the human capacity in training animals. The shows have gained impulse as a leisure space in the Roman Empire with the creation of amphitheaters, characterized as circus-hippodromes. At the end of the 18th century the modern circus was born that is the result of two universes conjunction: the English equestrian art, which was developed in barracks; and the feats of the acrobats, founded by English military Philip Astley (BOLOGNESI, 2002). Finally, the modern circus is characterized for presenting many circus attractions, such as animal presentations, acrobatic jumps, pantomimes, dances, and clowns.